Comparative Life Cycle Assessment of Carbon Emissions and Circular Economy in Conventional and Geopolymer Precast Concrete - Muhammad Fatoni Uhrowi; Jauhar Fajrin; I Ketut Budastra; Martin Anda (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
The construction sector accounts for approximately 37% of global carbon emissions, largely due to Portland cement production. Accelerated infrastructure development on Lombok Island has surged precast concrete demand, increasing the regional carbon footprint. This study compares the environmental impacts of conventional precast concrete against fly ash-based geopolymer concrete using Life Cycle Assessment (LCA) integrated with circular economy analysis. A cradle-to-gate boundary (Modules A1-A3) with a 1 m³ functional unit of K-350 concrete was modeled in OpenLCA using the CML-IA method. Primary data came from a West Lombok precast producer; the geopolymer mix was literature-based. Results indicate the conventional precast footprint is 381.71 kg CO₂-eq/m³, dominated by cement (90.40%). Substituting 90% cement with Jeranjang power plant fly ash reduced emissions by 49.15% to 194.10 kg CO₂-eq/m³, despite burden shifting to alkali activators (66.86% contribution). Binder circularity achieved 90%, with a fly ash supply-to-demand ratio of ~530%. A 2025–2029 projection shows potential avoidance of 20,027 tons CO₂-eq and absorption of 27,179 tons of fly ash. Sensitivity analysis confirms model robustness (±0.14%). Transitioning to geopolymer concrete is a highly recommended decarbonization strategy for West Nusa Tenggara.